Evaluation of superior lines of F4 generation derived from the cross Improved Samba Mahsuri X YPK267 for yield and yield related traits - R.M. SUNDARAM, P. JAYAMMA, CH. ANURADHA, P. SENGUTTUVEL, T. RAMESH and (The Journal of Research, PJTSAU, 2020)
Rapid population growth and global demandfor rice consumption has been estimated to rise from700 million tons (mt) to 852 mt in 2035. In India, wherepopulation is steadily growing, there is a need toincrease rice production from 103 mt to at least 136 mtby the year 2050 (http://www.icar-iirr.org/IIRR%20Vision% 202050.pdf). Therefore, improvement in theyield potential of rice has to be the major strategy tomeet the global rice demand. It is becoming increasinglydifficult to break yield ceiling by using conventionalbreeding (Peng et al.,1999). Grain yield in rice is acomplex trait determined by its three component traits:number of panicles, number of grains per panicle, andgrain weight; which are typical quantitative traits. Thepresent study was aimed to enhance yield potentialof Improved Samba Mahsuri (ISM) using markerassisted selection for presence of yield target traits i.e.high grain number, strong culm and panicle branchingwhich are governed by the genes Gn1a, SCM2 andOsSPL14 respectively. Phenotypic evaluation of F4population derived from the cross ISM Ã— YPK-267 wascarried out for growth and yield related traits. Promisinglines were identified for further use in rice breedingprograms.